The relationship between blood flow impairment and oxygen depletion in acute ischemic stroke imaged with magnetic resonance imaging. Issue 3 (March 2019) - Seiler, Alexander; Blockley, Nicholas P; Deichmann, Ralf; Nöth, Ulrike; Singer, Oliver C; Chappell, Michael A; Klein, Johannes C; Wagner, Marlies
Oxygenation-sensitive spin relaxation time T2′ and relaxation rate R2′ (1/T2′) are presumed to be markers of the cerebral oxygen extraction fraction (OEF) in acute ischemic stroke. In this study, we investigate the relationship of T2′/R2′ with dynamic susceptibility contrast-based relative cerebral blood flow (rCBF) in acute ischemic stroke to assess their plausibility as surrogate markers of the ischemic penumbra. Twenty-one consecutive patients with internal carotid artery and/or middle cerebral artery occlusion were studied at 3.0 T. A physiological model of the cerebral vasculature (VM) was used to process PWI raw data in addition to a conventional deconvolution technique. T2′, R2′, and rCBF values were extracted from the ischemic core and hypoperfused areas. Within hypoperfused tissue, no correlation was found between deconvolved rCBF and T2′ ( r  = −0.05, p  = 0.788), or R2′ ( r  = 0.039, p  = 0.836). In contrast, we found a strong positive correlation with T2′ ( r  = 0.444, p  = 0.006) and negative correlation with R2′ ( r  = −0.494, p  = 0.0025) for rCBFVM, indicating increasing OEF with decreasing CBF and that rCBF based on the vascular model may be more closely related to metabolic disturbances. Further research to refine and validate these techniques may enable their use as MRI-based surrogate markers of the ischemic penumbra for selecting stroke patients for interventional treatment strategies.